Risk Ownership in Contract Manufacturing - Ülkü, Sezer; Toktay, L. Beril; Yücesan, Enver (Manufacturing and Service Operations Management, 2007)
We consider a supply chain where a contract manufacturer (CM) serves a number of original equipment manufacturers (OEMs). Investment into productive resources is made before demand realization, hence the supply chain faces the risk of under- or overinvestment. The CM and OEMs differ in their forecast accuracy and in their resource pooling capabilities, leading to a disparity in their ability to minimize costs due to demand uncertainty. We consider two scenarios in which this risk is borne by the OEM and CM, respectively. We determine which party should bear the risk so that maximum supply chain profits are achieved. We investigate the effectiveness of premium-based schemes in inducing the best party to bear the risk, and conclude that they function well despite information asymmetry when double marginalization is not very high.